A critique on the rome statute: lacuna in its definition / Mohd Fairuz Amir Nazarullah...[et al.] - Amir Nazarullah, Mohd Fairuz; Mohd Zulkifli, Mohd Syakil; Zainal Abidin, Puteri Nur Afiza (2007)
This project paper aims to make recommendations on the improvements of certain definitions which are inadequate or lacking in the Rome Statute, specifically the definitions for crimes of aggression and war crimes. The works of various international groups to help come up with acceptable and comprehensive definitions in particular the definition of crimes of aggression are also included in this research paper. There is also a need to include the proviso of crimes against peace into each existing definition of war crimes in the Rome Statute i.e. genocide, war crimes, crimes against humanity and crimes of aggression. This part will be largely based on Luis Moreno-Ocampo, Chief Prosecutor of the International Criminal Court letter which says that with the incorporation of the provision of crimes against humanity into the existing categories of crimes in the Rome Statute, this would enable the aggrieved parties of war to take legal actions against their perpetrator which currently they are unable to do. Lastly, the most important objective of this research is to educate the international community about the importance of the Rome Statute in terms of their rights in times of war. This is especially so because in present day, we see that nations of the world are more inclined to resort to the acts of war to resolve their dispute or gain something. Therefore, if the international community is well aware about the Rome Statute and their rights in it, they will be able to take legal actions in cases of their rights are violated by the other country.